2021
DOI: 10.1002/ceat.202100127
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of a Benzene‐Toluene Mixture Using Metal Nanoparticles Stabilized by a Hyper‐Crosslinked Aromatic Polymer

Abstract: Hydrogenation of aromatic compounds is a widely used catalytic process in modern industry. Selective hydrogenation of benzene (BZ)-toluene (TL) mixtures is an important industrial process as it allows the purification of BZ for further synthetic purposes. In this work, the hydrogenation of a BZ-TL mixture (at a molar ratio close to 1) was studied for varying reaction parameters (temperature in the range of 100-180 °C and pressure in the range of 1-7 MPa) using Pt-, Pd-, and Ru-containing nanoparticles stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Both monometallic (Pd) and bimetallic (PdAu, PdCu and PdZn) catalysts containing 0.5–1.5 wt.% of Pd (data of XFA) and about 2 wt.% of a second metal were synthesized using HPS as a support. It was shown that independently in the presence of a second metal, palladium acetate is uniformly distributed in a highly porous aromatic network of HPS, which allows formation of small Pd NPs of about 2 nm in diameter after reduction in a hydrogen flow at 300 °C (the limit of temperature stability of the chosen HPS [ 40 ]). In the case of the Pd(CH 3 COO) 2 precursor, such reduction conditions are suitable for fast growth of metallic NPs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both monometallic (Pd) and bimetallic (PdAu, PdCu and PdZn) catalysts containing 0.5–1.5 wt.% of Pd (data of XFA) and about 2 wt.% of a second metal were synthesized using HPS as a support. It was shown that independently in the presence of a second metal, palladium acetate is uniformly distributed in a highly porous aromatic network of HPS, which allows formation of small Pd NPs of about 2 nm in diameter after reduction in a hydrogen flow at 300 °C (the limit of temperature stability of the chosen HPS [ 40 ]). In the case of the Pd(CH 3 COO) 2 precursor, such reduction conditions are suitable for fast growth of metallic NPs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A selectivity of 44% toward cyclohexane and an almost complete conversion of benzene were achieved under optimal conditions using Ru as the active metal ligand (see overview in Figure 6J). 60 In another study, Pd-derived HCPs (Figure 6K) catalyzed C−H halogenation, acetoxylation, and arylation with yields up to 85%, 75%, and 70%, respectively (see some examples of halogenation reactions in Figure 6L). These HCPs were based on N,N′-dimethyl-benzimidazolium iodide and triphenylmethane.…”
Section: Hyper-cross-linked Polymersmentioning
confidence: 97%
“…(J) Hydrogenation of a benzene/toluene mixture by a Ru-based HCP, with SEM image and benzene conversion under different conditions . Reprinted with permission ref . Copyright 2021, Wiley.…”
Section: Wide Range Of Applications For Hyper-cross-linked Polymersmentioning
confidence: 99%
See 2 more Smart Citations